The prevalence of Staphylococcus aureus and the emergence of livestock-associated MRSA CC398 in pig production in eastern China - Zheng, Lina; Jiang, Zhongyi; Wang, Zhenyu; Li, Yang; Jiao, Xinan; Li, Qiuchun; Tang, Yuanyue (Frontiers in Microbiology, 2023)
Livestock-associated Staphylococcus aureus (LA-MRSA) has been of increasing concern due to its potential risk to humans. This study investigated the prevalence of MRSA in pig production in Eastern China and determined the genomic characteristics of pig-associated MRSA isolates by whole-genome sequencing (WGS). A total of 1,318 samples were collected from pig farms and pig slaughterhouses, and 150 S. aureus were identified, including 63 MRSA isolates and 87 MSSA isolates. MRSA was detected in all pig farms and pig slaughterhouses. The antimicrobial susceptibility test revealed that all MRSA isolates were multidrug-resistant. The WGS and MLST analysis demonstrated that 56 MRSA isolates belonged to clonal complex (CC) 398, and seven MRSA isolates belonged to CC9. All LA-MRSA isolates were absent of phiSa3 phage containing immune evasion cluster (IEC) and possessed an intact hlb gene. In addition, genes associated with Panton-Valentine leukocidin, typically indicative of human adaptation, were not detected. The analysis of antibiotic resistance genes (ARGs) demonstrated that all MRSA isolates contained multiple ARGs. All MRSA isolates had Plthe mecA gene and at least one tetracycline resistance gene. Both tetM and tetK were detected in all MRSA CC398 isolates, while tetL was detected in all MRSA CC9 isolates. The phenicol resistance gene fexA was detected in 51 MRSA isolates, while the linezolid resistance gene cfr was detected in 60 MRSA isolates. The emergence of LA-MRSA CC398 in four pig farms and one slaughterhouse in this study indicates the spread of this clonal complex in the pig production sector in Eastern China. Further investigations are required to understand the potential transmission routes of LA-MRSA CC398 within the pork production chain in China and to assess the potential risks to humans.